The Effect of Gemu Famire Exercise on Emotional Level in Elderly with Chronic Diseases - Siti Juwariyah; Dewi Sekar Arum; Asti Nuraeni (Journal of Language and Health, 2025)
Emotional problems in the elderly can be caused by a decline in physical condition and the presence of chronic diseases experienced by the elderly. The impact of emotional disturbances in the elderly can lead to feelings of loss, loneliness, fear, depression, and can affect their daily activities. This study aims to analyze the effect of Gemu Famire gymnastics on the emotional levels of elderly individuals with chronic diseases. Method: This research is quantitative research with a pre-experimental one-group pre-posttest design research approach. The sample size in this study is 37 respondents in one group, using the purposive sampling technique. The research instrument for this study is the Self Report Questionnaire (SRQ). Based on the Wilcoxon test, the research results showed that there was an effect of Gemu Famire exercise on the emotional level of elderly individuals with chronic diseases, with a p-value of 0.000 (<0.05). The Gemu Famire exercise action plan can be done regularly by elderly individuals with chronic diseases to reduce emotional levels. The follow-up plan for Gemu Fa Mi Re exercise can be carried out periodically by elderly individuals with chronic diseases to reduce emotional levels, accompanied by community health workers.